2021
DOI: 10.1158/0008-5472.can-20-1741
|View full text |Cite
|
Sign up to set email alerts
|

A Very Long-Acting PARP Inhibitor Suppresses Cancer Cell Growth in DNA Repair-Deficient Tumor Models

Abstract: PARP inhibitors are approved for treatment of cancers with BRCA1 or BRCA2 defects. In this study, we prepared and characterized a very long-acting PARP inhibitor. Synthesis of a macromolecular prodrug of talazoparib (TLZ) was achieved by covalent conjugation to a PEG40kDa carrier via a β-eliminative releasable linker. A single injection of the PEG∼TLZ conjugate was as effective as ∼30 daily oral doses of TLZ in growth suppression of homologous recombination-defective tumors in mouse xenografts. These included … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…We previously showed that PEG$TLZ maintains a controlled and slow release of TLZ over $1 week in mice (Fontaine et al, 2021). Furthermore, the long elimination half-life, high tumor uptake, and very low efflux rates from tumors have been validated by PET imaging of PEG 40kDa -89 Zr conjugates (Beckford Vera et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We previously showed that PEG$TLZ maintains a controlled and slow release of TLZ over $1 week in mice (Fontaine et al, 2021). Furthermore, the long elimination half-life, high tumor uptake, and very low efflux rates from tumors have been validated by PET imaging of PEG 40kDa -89 Zr conjugates (Beckford Vera et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Recent preclinical and clinical trials of the experimental combination of talazoparib (TLZ), the most potent of the approved PARP1 inhibitors, and TMZ in Ewing sarcoma demonstrated notable antitumor activity, but the combination was toxic both in patients and in mice (Schafer et al, 2020;Smith et al, 2015). As an alternative therapeutic approach to reducing toxicity and improving efficacy of the drug combination, we evaluated a novel PEGylated conjugate of TLZ (PEG$TLZ) that allows sustained, controlled release of the inhibitor within the tumor microenvironment (Fontaine et al, 2021). Nanocarrier-linked drugs increase uptake into tumor tissue and reduce permeability to normal vasculature, leading to lower dose exposure in normal tissues and reduced toxicity (Van De Ven et al, 2017, Caster et al, 2015Tsouris et al, 2014;Maeda et al, 2000;Baldwin et al, 2019;Chauhan and Jain, 2013;Chauhan et al, 2012;Matsumura and Maeda, 1986;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were handled according to the approved protocol (18-174) and all mice were maintained in a 12-h light/dark cycle and provided with water and standard diet ad libitum in a pathogen-free facility under climate control. 2 × 10 7 of the human LMS cells were inoculated into the right flank of mice with 1:1 Matrigel (Corning, Corning NY, USA) and fetal bovine serum (FBS) according to the previous publications [42][43][44][45][46]. After the tumor development, the animals were randomized separately into three groups, SMO inhibitor LDE225 (n = 5), GLI inhibitor Gant61 (n = 6 × 2), and control (n = 6 × 2).…”
Section: Leiomyosarcoma Xenograft Tumorsmentioning
confidence: 99%
“…Bisphosphonates such as zoledronic acid can inhibit cancer angiogenesis, and because of their affinity to bone, nanoparticles conjugated with bisphosphonates showed an increased uptake and cell toxicity compared to pegylated PGLA nanoparticles [87,88]. Fontaine et al showed that long-acting PEGylated talazoparib has promising anti-tumor activity in Ewing sarcoma [89]. One approach to Ewing sarcoma involves silencing the miRNA that drives CD99, a hallmark surface antibody in the disease.…”
Section: Ewing Sarcomamentioning
confidence: 99%